Estimasi Biaya Perangkat Lunak menggunakan Metode Use Case Point (Studi Kasus: PT. Pln(Persero) Area Malang) - Habib Rahman Muhammad Akbar Putra; Widhy Hayuhardhika Nugraha Putra; Djoko Pramono (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
There are a number of problems encountered by companies related to project work, the problem about triple constraints on the project, namely time, cost and scope of the project. Calculation of time estimates that have not been standardized properly makes the project cost load can be over-estimated or under-estimated. The application of scientific method, namely Use Case Point (UCP) can be used as one of the standardization calculations for a project's time estimation, this is the purpose this study with the object Sistem Konstruksi Tiang on PT. PLN (Persero) Area Malang , therefore in this study scheduling uses Gantt Chart which refers to the Work Breakdown Structure or WBS. In this study using the UCP method resulted in an estimated time of 411.04 hours and estimated costs of Rp20,383,062.50.